Religion, gender, course and ethnic differences in students’ ethical awareness - Azizan Had; Starry Garijih (2017)
The research tries to answer the question of 'does religion, education and social surroundings play a role in developing students' ethical behaviour?' To understand more on the topic, I have surveyed students at the Labuan branch of University Malaysia Sabah in malaysia, a public university where most of the students are taking a first degree in Business and Computer Studies. Using a survey questionnaire, I test five important hypotheses: whether ethical attitudes are affected by religiosity, religion, social life, university education and by what happens around them at home. The result shows that ethical awarenss is mostly determined by religion. In addition, the findings also shows that ethnicity also play a role in a students' awareness of ethical values.